Preparation method of bionic double-layer aerogel thermal fabric

Through the preparation method of bionic double-layer aerogel warm-insulating fabric, low-temperature oxygen plasma treatment and enzyme finishing technology are used to form multi-stage branch groove structures and nano-scale pores, solving the shortcomings of existing warm-insulating fabrics in terms of lightweight, moisture permeable and breathable, and long-term durability, achieving efficient warmth and comfortable wear.

CN120486119APending Publication Date: 2025-08-15KANGDIYA (JIANGSU) NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510547212.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

The existing warm fabrics have shortcomings in lightweight, moisture-permeable and breathable, and long-term durability, making it difficult to achieve efficient warmth and comfortable wear.

Method used

The preparation method of bionic double-layer aerogel warm-inhibited fabric is adopted. By weaving the double-layer tissue fabric, combining low-temperature oxygen plasma treatment, cellulase finishing and protease/lipase treatment, as well as chitosan/water-based polyurethane coating, multi-stage branch groove structure and nano-scale pores are formed to improve thermal insulation and hygroscopicity.

Benefits of technology

It achieves comprehensive performance of high efficiency, moisture permeability, breathability and long-term durability, enhances the insulation and comfort of the fabric, and reduces thermal convection and heat radiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005381070600000151
    Figure BDA0005381070600000151
  • Figure BDA0005381070600000161
    Figure BDA0005381070600000161
Patent Text Reader

Abstract

The invention provides a preparation method of a bionic double-layer aerogel thermal fabric, which comprises the following steps: S1, weaving a double-layer texture fabric, selecting superfine polyester as warp yarns and aerogel modified polyester and spandex as weft yarns in a surface texture, and selecting modal fibers as warp yarns and weft yarns in a lining texture; s2, performing low-temperature oxygen plasma treatment on one side of the inner texture of the double-layer texture fabric; s3, soaking the fabric subjected to plasma treatment in a finishing liquid containing cellulase for finishing; s4, after drying the finished fabric, soaking the fabric in a mixed finishing liquid containing protease / lipase for finishing to obtain a protease / lipase finished fabric; and S5, coating one side of the inner tissue of the fabric subjected to protease / lipase finishing with the salt-containing chitosan / waterborne polyurethane finishing liquid, drying, and washing to dissolve out salt, so as to obtain the warm-keeping fabric. According to the invention, material modification and structural design are combined, so that high-efficiency thermal insulation performance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fabrics, and in particular to a method for preparing a bionic double-layer aerogel thermal insulation fabric. Background Art

[0002] Traditional thermal fabrics mainly form a static air layer by increasing the thickness of the material or constructing a fluffy structure (such as the natural curl of down and wool, and the fiber entanglement of fleece), and achieve thermal insulation and warmth by reducing heat convection and heat conduction. Common materials can be divided into three categories: 1. Natural fibers: Cotton: relies on the hollow structure of the fiber (8.5% regain) to accumulate air, but the thermal conductivity increases by 50% after moisture absorption, and the drying speed is slow (evaporation rate <0.3g / h), which can easily lead to low temperature coldness; Wool: relies on the scale layer (17-20 layers / mm) to form natural curls and pores, and can still maintain 80% warmth in a wet state, but the fiber diameter is coarse (>20μm), resulting in a thick fabric (surface density >300g / m 2 ) and easily cause skin itching; 2. Chemical fiber: Polyester / Acrylic: The specific surface area is increased by using special-shaped cross-sections (such as hollow, trilobal) or ultra-fine fibers (<0.5dtex), and the fluffiness can be up to 1.5 times that of natural down, but the hydrophobicity leads to electrostatic adsorption of dust, and the air permeability is low (<100mm / s); 3. Composite material: Metal-coated fabric: The aluminized film reflects human infrared radiation (reflectivity>85%), but the high rigidity of the coating causes the bending stiffness of the fabric to increase by 200%, affecting wearing comfort. In recent years, new thermal insulation technologies have achieved breakthroughs through the intersection of materials science and engineering: for example, phase change materials (PCMs): paraffin wax, fatty acids, etc. are encapsulated in microcapsules (diameter 2-50 μm) and implanted into fibers, absorbing / releasing heat through solid-liquid phase change (enthalpy value 80-200 J / g). For example, The fiber can dynamically adjust the temperature in the range of 28-32°C, but there are bottlenecks such as poor cyclic stability (enthalpy decay >40% after 500 cycles) and decreased air permeability (coating closes pores); far-infrared heating fiber: Fibers with added ceramic particles (such as zirconium carbide and aluminum oxide) can absorb human body radiation (wavelength 8-14um) and re-emit it, with a temperature increase of 2-5°C, but the emission efficiency is significantly affected by humidity; aerogel composite material: After silica aerogel (porosity >95%) is compounded with a fiber matrix, the thermal conductivity is as low as 0.016W / m·K, but it is highly brittle and has processing temperature restrictions, making it difficult to directly apply it in the textile field. Although these technologies have improved lightweight and dynamic response capabilities (PCM temperature adjustment span > 10°C), they still face multiple contradictions: natural materials are environmentally friendly but have limited performance, chemical materials are highly efficient but have environmental burdens, and new technologies are often expensive (aerogel fabric price > US$200 / m 2 ) or the process is complex (the microcapsule encapsulation rate needs to be precisely controlled within ±5%). Summary of the Invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a bionic double-layer aerogel thermal insulation fabric, which achieves the comprehensive performance of high-efficiency thermal insulation, moisture permeability and breathability, and long-term durability through the combination of material modification and structural design.

[0004] Technical solution: A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. weaving a double-layer fabric, wherein the outer fabric uses ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner fabric uses modal fiber as the warp yarn and the weft yarn; S2. The inner side of the double-layer tissue fabric is treated with low-temperature oxygen plasma; S3. The plasma-treated fabric is immersed in a finishing solution containing cellulase for finishing; S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase to obtain a protease / lipase-finished fabric; S5. Coat the inner tissue side of the protease / lipase treated fabric with a salt-containing chitosan / aqueous polyurethane finishing solution, dry it, and then wash away the salt to obtain a warm fabric. Preferably, the specification of the ultrafine polyester is 88.8-133.2 dtex / 288-432 f, the specification of the aerogel-modified polyester is 44.4-66.6 dtex / 12-24 f, the specification of the spandex is 4.4 tex; the specification of the modal fiber is 50 dtex / 36-48 f; and / or, The double-layer fabric is joined by the inner warp stitching method, the outer weave of the double-faced fabric is a basket weave, the inner weave is a plain weave, and the stitching weave is a satin weave; and / or, The warp density of the surface fabric is 280-320 strands / inch, and the weft density is 140-150 strands / inch; the warp density of the lining fabric is 150-170 strands / inch, and the weft density is 130-140 strands / inch. Preferably, the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber is plasma treated to obtain a plasma-treated polyester fiber; S12. Add the polyester fiber prepared in step S11 to the silica sol, immerse it, take it out, and place it in anhydrous ethanol for solvent replacement to obtain aerogel-modified polyester. Preferably, the cross section of the modal fiber of the inner structure is a special-shaped cross section, and the special-shaped cross section is a triangle, a cross or a sawtooth. Preferably, the parameters of the low-temperature oxygen plasma treatment in step S2 are: power of 30 to 50 W, time of 2 to 4 minutes, and pressure of 10 to 20 Pa. Preferably, the finishing method in step S3 is to apply a tension of 5 to 20 N / cm to the fabric during the finishing process, first finishing at 45 to 50°C for 5 to 10 minutes, removing the finishing liquid on the surface of the fabric after washing and cleaning, and then immersing it in the finishing liquid for 2-3 times and applying a tension of 5 to 10 N / cm for 3 to 5 minutes; wherein the content of cellulase in the finishing liquid is 0.2 to 0.8 g / L, the pH of the finishing liquid is 4.0 to 5.0, and the bath ratio is 1:30 to 50. Preferably, in step S4, the protease is serine protease, the lipase is lipoprotein lipase, the concentrations of the lipase and protease in the finishing solution are both 0.5-2 g / L, the pH of the finishing solution is 6.5-7.5, the finishing time is 1-3 h, and the bath ratio is 1:30-50. Preferably, the method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 3 to 6 wt%; S22. Aqueous polyurethane having a mass fraction of 15 to 25 wt% is mixed with a chitosan solution in a volume ratio of 1:2 to 3, and sodium chloride is added after stirring evenly. The amount of sodium chloride in the mixed solution is 3.5 to 6.5 wt%. The mixture is stirred evenly to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Preferably, the coating amount of the salt-containing chitosan / aqueous polyurethane finishing liquid on the fabric surface is 5 to 15 g / m 2 . Preferably, the basket weave is any one of a 2 / 2 basket weave, a 3 / 3 basket weave or a 4 / 4 basket weave. Beneficial effects: The bionic double-layer aerogel thermal insulation fabric of the present invention has the following advantages: 1. In this invention, aerogel-modified fiber + spandex is used as the weft yarn and ultrafine polyester is used as the warp yarn in the surface weave of the double-layer fabric to create a highly efficient thermal insulation layer. The aerogel-coated polyester fiber in the weft yarn gives the weft yarn surface a nano-scale pore structure, significantly reducing heat radiation and convection heat dissipation. The warp yarn uses ultrafine polyester fiber with a smaller fiber diameter, which can form a denser yarn structure, reduce air flow, and enhance warmth retention. Compared with ordinary polyester, ultrafine fiber has a larger specific surface area, can absorb more still air, and improve thermal resistance. 2. The fabric structure of the present invention is designed as a double-layer structure. The outer fabric adopts a basket weave. The precise structure of the basket weave can relatively reduce the exchange of hot and cold air. The inner fabric adopts soft and skin-friendly modal fiber to improve wearing comfort. After the outer and inner fabrics are connected, a stable and static air layer is formed between the outer and inner fabrics, which reduces heat convection and improves warmth retention. 3. In the present invention, the fabric is first treated with low-temperature oxygen plasma in the finishing part to form micron-sized grooves on the surface of the modal fiber of the lining. After the plasma treatment, cellulase is used for enzymatic hydrolysis. During the enzymatic hydrolysis process, a certain tension is applied to the fabric. Through the effects of enzymatic hydrolysis and tension, multi-level branched grooves are further formed in the micron-sized grooves, thereby improving the moisture absorption and heat generation effect of the lining. 4. In the present invention, the fabric is loaded with lipase and protease, which can decompose the oil / protein in sweat, prevent clogging of micropores and grooves, etc., maintain long-term moisture absorption and heat generation effects, and is coated with chitosan / polyurethane coating to ensure long-term adhesion of the enzyme and improve the number of water washing resistance. DETAILED DESCRIPTION The present invention will be further described below in conjunction with examples, which are provided to explain the present invention and are not limited to the following examples: A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving double-layer fabrics, with superfine polyester as the warp and aerogel-modified polyester + spandex as the weft for the outer weave, and modal fiber as the warp and weft for the lining. S2. The inner side of the double-layer tissue fabric is treated with low-temperature oxygen plasma; S3. The plasma-treated fabric is immersed in a finishing solution containing cellulase for finishing; S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase to obtain a protease / lipase-finished fabric; S5. Coat the inner tissue side of the protease / lipase treated fabric with a salt-containing chitosan / aqueous polyurethane finishing solution, dry it, and then wash away the salt to obtain a warm fabric. The fabric structure of S1 is a double-layer fabric, which is joined by the inner warp stitching method. The surface fabric of the double-faced fabric is a basket weave, the inner fabric is a plain weave, and the stitching fabric is a satin weave. The specifications of the ultrafine polyester are 88.8-133.2dtex / 288-432f, the specifications of the aerogel-modified polyester are 44.4-66.6dtex / 12-24f, and the specifications of the spandex are 4.4tex; the specifications of the modal fiber are 50dtex / 36-48f; the surface fabric of the double-layer fabric is a basket weave, which has high coverage and can reduce the penetration of cold air, thereby improving the windproofness of the surface layer. Ultrafine polyester fiber and aerogel-modified polyester (44.4-66.6dtex / 12-24f) are used to avoid condensation. The rubber particles fall off to ensure long-term warmth retention. The microfiber has a smaller fiber diameter, which can form a denser yarn structure, reduce air flow and enhance warmth retention. The tight structure of the plain weave lining reduces air flow in the inner layer and reduces contact thermal resistance (heat conduction loss between the skin and the fabric). Modal fiber is selected as the material, which has high hygroscopicity (moisture regain of 12%, better than cotton) and can absorb moisture evaporated from the skin to avoid the "evaporative cooling effect" caused by sweat retention. Satin is used to connect the surface and lining. The satin connection method is characterized by fewer connection points and reduced thermal bridge effect. The binding yarn (ultrafine polyester 88.8~133.2dtex / 288~432f) runs through the surface and inner layers in the form of long floating lines. The high specific surface area of the ultrafine polyester binding yarn can absorb more still air, further improving thermal insulation. In S2, low-temperature oxygen plasma is used to treat modal fibers. The high-energy active particles (O + 、O2 + The surface of the modal fiber is bombarded with plasma (e.g., plasma ionization, etc.), and the amorphous area is selectively etched to form microgrooves / micropores. The microgroove structure can capture more still air, forming a nano-micron composite air layer on the fiber surface, making the heat conduction path tortuous and reducing the effective thermal conductivity. At the same time, plasma oxidation introduces polar groups such as -C=O and -COOH on the fiber surface, thereby improving the fiber's reflectivity to far-infrared rays (8-14μm). The microgroove structure reflects the human body's radiant heat back to the skin through the multiple scattering effect, and cooperates with the aerogel-modified polyester fiber to form a "reflection-barrier" dual-effect thermal insulation system. In S3, plasma-pretreated modal fibers are biomimetically etched using cellulase to form a micro-nano groove structure with multi-level branches and self-similarity (similar to the veins / root branches of leaves). The fractal structure changes the distribution of static air from a single layer to a gradient multi-layer. The plasma-etched grooves in the multi-level branched groove mold serve as the main channel for rapid moisture conduction. The branches after cellulase hydrolysis can expand the evaporation area and improve the moisture absorption and heat generation effect of the inner tissue. In S4, the fabric is loaded with lipase and protease, which can break down the oil / protein in sweat, prevent clogging of micropores and grooves, maintain long-term moisture absorption and heat generation effects, and is coated with chitosan / polyurethane coating to ensure long-term adhesion of the enzyme and improve the number of washes. The modal fibers in the S1 fabric have a shaped cross-section, perhaps a triangle, a cross, or a zigzag. The special shape of these fibers increases the cohesion between the fibers, thereby enhancing their bulk. This bulk allows the fibers to trap more air, forming an insulating layer and thus enhancing warmth. The presence of grooves and holes on the fiber surface significantly enhances the capillary effect. This capillary effect helps to quickly draw moisture and perspiration away from the skin, keeping the fabric dry and comfortable, and indirectly improving warmth retention. The parameters of low-temperature oxygen plasma treatment in S2 are: power of 30-50W, time of 2-4min, and pressure of 10-20Pa. The above parameters are sufficient to break the chemical bonds on the fiber surface and induce etching, thereby avoiding deep damage. The power range of 30-50W can provide enough energy to activate oxygen molecules (generating O·, O2 + Low-temperature plasma etching can not only reduce the amount of high-activity groups (such as carbon atoms), but also avoid thermal degradation of the fiber or excessive surface etching caused by excessive power. At lower power, the electron density and ion energy distribution in the plasma are more uniform, which helps to form a regular surface groove structure. If the low-temperature plasma etching time is too short (such as <2 minutes), it may lead to insufficient introduction of surface functional groups or insufficient groove depth. If the etching time is too long (such as >4 minutes), it may lead to uneven surface roughness or degradation of fiber performance due to over-etching. At a moderate pressure of 10-20 Pa, the mean free path of gas molecules is short, the frequency of collisions between electrons and gas molecules increases, and the plasma density is significantly improved. This is conducive to enhancing the generation efficiency of oxygen free radicals (O·) and promoting chemical oxidation reactions on the fiber surface. The finishing method in S3 is to apply 5-20N / cm tension to the fabric during the finishing process, first finishing at 45-50℃ for 5-10min, then remove the finishing liquid on the surface of the fabric after washing, and then repeat 2-3 times to immerse it in the finishing liquid and apply 5-10N / cm tension for 3-5min; the content of cellulase in the finishing liquid is 0.2-0.8g / L, the pH of the finishing liquid is 4.0-5.0, and the bath ratio is 1:30-50; the groove structure after plasma etching (such as nano-scale roughness) increases the specific surface area, and the tension further stretches the fiber surface, exposing more non-crystalline areas of cellulose chains, so that the enzyme molecules (optimum pH 4.0-5.0) is easier to adsorb and catalyze hydrolysis; under a tension of 5-20 N / cm, the molecular chains of the fiber are arranged along the stretching direction, resulting in the enzymatic hydrolysis preferentially proceeding in the direction perpendicular to the chain (similar to anisotropic etching), thereby forming regular transverse branch grooves; repeated dipping process (2-3 times) combined with tension loading can achieve step-by-step refinement of multi-level branch grooves: initial finishing: main grooves and primary branches are formed under higher tension (15-20 N / cm); subsequent dipping: tension is reduced to 5-10 N / cm, and the stress concentration effect of the main groove is used to induce secondary branches, forming a surface morphology similar to a fractal structure. The bath ratio of 1:30-50 ensures that the finishing liquid fully covers the fiber surface, while avoiding excessive hydrolysis caused by excessive enzyme concentration that destroys the structural integrity. Example 1 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 20 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution for 5 min and a tension of 5 N / cm was applied. The finishing solution contained 0.2 g / L cellulase, had a pH of 5.0, and a bath ratio of 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Example 2 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 20 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and a tension of 5 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.5 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Example 3 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 20 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and a tension of 5 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Example 4 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 10 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After removing the finishing solution from the surface of the fabric, the surface was washed and cleaned. The fabric was then immersed in the finishing solution twice and a tension of 5 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Example 5 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 10 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and the tension of 10 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Comparative Example 1 A method for preparing a bionic gas gel thermal insulation fabric, the method comprising the following steps: S1. Woven fabric: The fabric adopts plain weave, with ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn. The specifications of ultrafine polyester are 88.8dtex / 288f, the specifications of aerogel-modified polyester are 44.4dtex / 12f, and the specifications of spandex are 4.4tex. S2. One side of the fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 20 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and a tension of 5 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. Coat one side of the protease / lipase treated fabric with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , after drying, washing and dissolving the salt to obtain a warm fabric; Wherein, the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Comparative Example 2 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 10 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and cleaned from the surface of the fabric, the fabric was immersed in the finishing solution twice and the tension of 10 N / cm was applied for 5 min. The cellulase content in the finishing solution was 5 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Comparative Example 3 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 50 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and a tension of 20 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Comparative Example 4 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 20 N / cm was applied to the fabric and the finishing was performed at 45°C for 10 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , drying and washing to dissolve the salt, thereby obtaining a warm fabric; wherein the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. The polyester fiber prepared in step S11 is added to the silica sol, immersed therein, and then removed and placed in anhydrous ethanol for solvent replacement to obtain an aerogel-modified polyester; The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Comparative Example 5 A method for preparing a bionic double-layer thermal insulation fabric, comprising the following steps: S1. Weaving double-layer fabric, double-layer fabric using the inner warp binding method, double-face fabric surface tissue using 4 / 4 square basket weave, the inner tissue using plain weave, the binding tissue using 8 satin weave, the surface tissue using ultrafine polyester as warp yarn and polyester + spandex as weft yarn, the inner tissue using modal fiber as warp and weft yarn, the ultrafine polyester specification is 88.8dtex / 288f, the polyester specification is 44.4dtex / 12f, the spandex specification is 4.4tex; the modal fiber specification is 50dtex / 36f, the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 10 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and the tension of 10 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase for finishing, wherein the protease was a serine protease and the lipase was a lipoprotein lipase. The concentrations of the lipase and protease in the finishing solution were 1 g / L, the pH of the finishing solution was 7, the finishing time was 2 h, the bath ratio was 1:40, and a protease / lipase-finished fabric was obtained; S5. The inner side of the fabric treated with protease / lipase is coated with a salt-containing chitosan / aqueous polyurethane finishing solution. The coating amount of the salt-containing chitosan / aqueous polyurethane finishing solution on the fabric surface is 7.5 g / m 2 , after drying, washing and dissolving salt to obtain a warm fabric; wherein, the preparation method of the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 4 wt%; S22. A 20 wt% aqueous polyurethane solution was mixed with a chitosan solution in a volume ratio of 1:2.5, and sodium chloride was added after stirring. The amount of sodium chloride in the mixed solution was 5 wt%. The mixture was stirred and mixed to obtain a salt-containing chitosan / aqueous polyurethane finishing solution. Comparative Example 6 A method for preparing a bionic double-layer aerogel thermal insulation fabric, the method comprising the following steps: S1. Weaving a double-layer fabric, the double-layer fabric is connected by the inner warp binding method, the surface weave of the double-faced fabric is 4 / 4 square weave, the inner weave is plain weave, and the binding weave is 8-piece satin weave. The surface weave is made of ultrafine polyester as the warp yarn and aerogel-modified polyester + spandex as the weft yarn, and the inner weave is made of modal fiber as the warp and weft yarn. The specification of the ultrafine polyester is 88.8dtex / 288f, the specification of the aerogel-modified polyester is 44.4dtex / 12f, and the specification of the spandex is 4.4tex; the specification of the modal fiber is 50dtex / 36f, and the cross-section is triangular; S2. The inner side of the double-layer fabric was treated with low-temperature oxygen plasma. The parameters of the low-temperature oxygen plasma treatment were: power 30W, time 4min, and pressure 10Pa; S3. The plasma-treated fabric was immersed in a finishing solution containing cellulase for finishing. During the finishing process, a tension of 10 N / cm was applied to the fabric. The fabric was first finished at 45°C for 10 min. After the finishing solution was removed and washed to clean the surface of the fabric, the fabric was immersed in the finishing solution twice and the tension of 10 N / cm was applied for 5 min. The cellulase content in the finishing solution was 0.8 g / L, the pH of the finishing solution was 4.0, and the bath ratio was 1:50. S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase, the protease was a serine protease, the lipase was lipoprotein lipase, the concentration of the lipase and protease in the finishing solution was 1g / L, the pH of the finishing solution was 7, the finishing time was 2h, the bath ratio was 1:40, to obtain a warm fabric; Wherein, the preparation method of the aerogel-modified polyester fiber is: S11. The polyester fiber was plasma treated at a power of 20 W for 5 min at a pressure of 15 Pa to obtain a plasma-treated polyester fiber; S12. Ethyl orthosilicate, deionized water, and ethanol were mixed in a ratio of 1:10:2 and the pH was adjusted to 10 to obtain a silica sol. S13. Add the polyester fiber prepared in step S11 to the silica sol, immerse it, take it out, and place it in anhydrous ethanol for solvent replacement to obtain aerogel-modified polyester. Experimental method: Refer to the standard GB / T11048-2008 "Determination of thermal and moisture resistance of textiles under steady-state conditions for physiological comfort". After the experiment begins, preheat the machine for 45 minutes. Place a piece of fabric on the test plate. After the test plate temperature reaches 35°C, remove the fabric. After the temperature of the heating plate and bottom plate reaches 35.2°C, place the test sample on the test plate. Set the experimental parameters, set the test plate temperature to 35°C, set the experimental time to 600 seconds, and take the average of the thermal resistance three times. Take the fabric and cut it into a 40cm*40cm square test piece. Weigh blood stains (0.2g), milk stains (0.2g), and sweat stains (0.2g) respectively, and evenly distribute them on the designated position of the fabric test piece. Use the finger wearing a cot to smear the stains into Mark the stained specimen. Place the stained specimen flat and suspended for 2 hours at room temperature. Simulate the washing test using a washing machine, using the same standard washing procedure. Repeat the contamination-then-washing procedure 10 times and measure the thermal resistance. Referencing the standard GB / T 29866-2013, "Test Method for Hygroscopic and Heat-Reducing Properties of Textiles," six fabric swatches were cut for each test sample. Two of the swatches were placed together with their reverse sides facing up. Using polyester thread, the three sides of the reverse-faced swatches were sewn together using a flat seam to form a bag-shaped sample. The maximum and average temperature rises of the fabric within 30 minutes were calculated by comparing the temperature with that of a blank test group and subtracting the temperature measured in the blank group. With reference to the standard GB / T 3923.2-2013 “Tensile properties of textile fabrics - Part 2: Determination of breaking strength”, the tensile breaking strength of the examples and comparative examples was tested (the warp and weft densities of the fabrics in the examples and comparative examples were the same). Warp breaking strength N Weft breaking strength N Example 1 656 477 Example 2 648 464 Example 3 659 466 Example 4 662 449 Example 5 660 457 Comparative Example 1 589 412 Comparative Example 2 605 423 Comparative Example 3 595 408 Comparative Example 4 649 461 Comparative Example 5 650 465 Comparative Example 6 634 424 As shown in Examples 1-3 and Comparative Example 2, increasing lipase content improves thermal insulation performance, but excessive enzymatic hydrolysis can lead to a decrease in mechanical properties. Examples 3-4 and Comparative Example 3 show that excessive tension during enzymatic hydrolysis can cause more chain breakage, leading to a decrease in mechanical properties. Comparative Example 4 shows that applying tension only once is less effective than applying tension multiple times for enzymatic hydrolysis, while also protecting the fabric's mechanical properties. Comparative Examples 5 and 6 show that the selection of gel fibers and the addition of coatings have a positive impact on thermal insulation performance. Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.

Claims

1. A method for preparing a bionic double-layer aerogel thermal insulation fabric, characterized in that: The preparation method comprises the following steps: S1. Weaving double-layer fabrics, with superfine polyester as the warp and aerogel-modified polyester + spandex as the weft for the outer weave, and modal fiber as the warp and weft for the lining. S2. The inner side of the double-layer tissue fabric is treated with low-temperature oxygen plasma; S3. The plasma-treated fabric is immersed in a finishing solution containing cellulase for finishing; S4. After drying the finished fabric, it was immersed in a mixed finishing solution containing protease / lipase to obtain a protease / lipase-finished fabric; S5. Coat the inner tissue side of the protease / lipase treated fabric with a salt-containing chitosan / aqueous polyurethane finishing solution, dry it, and then wash away the salt to obtain a warm fabric.

2. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: The specification of the ultrafine polyester is 88.8-133.2 dtex / 288-432 f, the specification of the aerogel-modified polyester is 44.4-66.6 dtex / 12-24 f, the specification of the spandex is 4.4 tex; the specification of the modal fiber is 50 dtex / 36-48 f; and / or, The double-layer fabric is joined by the inner warp stitching method, the outer weave of the double-faced fabric is a basket weave, the inner weave is a plain weave, and the stitching weave is a satin weave; and / or, The warp density of the surface fabric is 280-320 strands / inch, and the weft density is 140-150 strands / inch; the warp density of the lining fabric is 150-170 strands / inch, and the weft density is 130-140 strands / inch.

3. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: The preparation method of the aerogel-modified polyester fiber is as follows: S11. The polyester fiber is plasma treated to obtain a plasma-treated polyester fiber; S12. Add the polyester fiber prepared in step S11 to the silica sol, immerse it, take it out, and place it in anhydrous ethanol for solvent replacement to obtain aerogel-modified polyester.

4. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: The cross section of the Modal fiber of the inner structure is a special-shaped cross section, and the special-shaped cross section is a triangle, a cross or a sawtooth.

5. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: The parameters of the low-temperature oxygen plasma treatment in step S2 are: power of 30-50 W, time of 2-4 min, and pressure of 10-20 Pa.

6. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: The finishing method in step S3 is to apply a tension of 5 to 20 N / cm to the fabric during the finishing process, first finishing at 45 to 50° C. for 5 to 10 minutes, removing the finishing liquid on the surface of the fabric after washing and cleaning, and then immersing it in the finishing liquid for 2 to 3 times and applying a tension of 5 to 10 N / cm for 3 to 5 minutes; the content of cellulase in the finishing liquid is 0.2 to 0.8 g / L, the pH of the finishing liquid is 4.0 to 5.0, and the bath ratio is 1:30 to 50.

7. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: In step S4, the protease is serine protease, the lipase is lipoprotein lipase, the concentrations of the lipase and protease in the finishing solution are both 0.5-2 g / L, the pH of the finishing solution is 6.5-7.5, the finishing time is 1-3 hours, and the bath ratio is 1:30-50.

8. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 1, characterized in that: The method for preparing the salt-containing chitosan / aqueous polyurethane finishing liquid in step S5 comprises the following steps: S21. Dissolving water-soluble chitosan in water to obtain a chitosan solution having a concentration of 3 to 6 wt%; S22. Aqueous polyurethane having a mass fraction of 15 to 25 wt% is mixed with a chitosan solution in a volume ratio of 1:2 to 3, and sodium chloride is added after stirring evenly. The amount of sodium chloride in the mixed solution is 3.5 to 6.5 wt%. The mixture is stirred evenly to obtain a salt-containing chitosan / aqueous polyurethane finishing solution.

9. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 8, characterized in that: The coating amount of the salt-containing chitosan / aqueous polyurethane finishing liquid on the fabric surface is 5 to 15 g / m 2 .

10. The method for preparing the bionic double-layer aerogel thermal insulation fabric according to claim 2, characterized in that: The basket weave is any one of a 2 / 2 basket weave, a 3 / 3 basket weave or a 4 / 4 basket weave.

Citation Information

Cited By

  • Degradable soft cotton towel and preparation method thereof

    CN120759050A

  • Temperature regulating agent for leather and preparation method of temperature regulating agent

    CN120843064A